REGULASI TATA RUANG DAN HAK LINGKUNGAN: STUDI KEBIJAKAN PENGENDALIAN PERUBAHAN LAHAN DI BALI - Ni Wayan Eka Sumartini; Rahmida Erliyani; Erlina (VYAVAHARA DUTA, 2026)
Land conversion in Bali has become increasingly intensive in line with the rapid development of the tourism sector and the increasing need for organizational space and supporting infrastructure. Land conversion, particularly from agricultural land and protected areas to built-up areas, has given rise to various environmental, socio-cultural, and spatial use conflicts at the local level. This situation has resulted in a decline in the environmental carrying capacity and carrying capacity, and has direct implications for the granting of the community's constitutional right to a healthy and good environment. This article aims to analyze Bali's spatial planning regulations for controlling land conversion to ensure environmental sustainability and examine the protection of the right to a healthy and good environment within these regulations. This research is a juridical-normative study through an examination of spatial planning laws and regulations. The results indicate that, normatively, the spatial planning regulatory framework in Bali accommodates the principles of sustainable development and recognizes local wisdom. Guarantees for a healthy and good environment are also enshrined in Bali's spatial planning regulations.